English Verbs of Directional Vision:Compatibility with Designations of a Qualitative Attribute - N. A. Antonova; T. S. Ignatyeva (Научный диалог)
This article addresses the challenges of constructing a semantic model of verbs related to the concept of ‘directed vision process and its qualitative attribute’ based on English collocations. The authors examine the structure of meaning of these lexical items through the analysis of the collocational patterns of look, watch, glance, stare, and gaze. This classification can be seen as a step towards creating a typological semasiology of specific languages. The structure of the complex lexical meaning ‘directed vision process and its attribute’ can be broken down into the following components: the invariant meaning, i.e., the core sememe (directed vision process), and an additional semantic component, i.e., the subordinate sememe (qualitative attribute of the vision process). A comprehensive sample was taken from 8000 pages of text from 24 works of fiction, describing 927 collocations. The first group includes collocations expressing various negative emotions associated with directed vision process: bad mood, nervousness, distrust, unfriendliness, fear, hatred, contempt, cruelty, etc. The second group consists of collocations expressing attentiveness, steadfastness, surprise, curiosity, wonder in characterizing directed gaze. The third group combines collocations expressing activity, speed, brevity, stealth of a brief glance. The authors came to the conclusion that all vision lexemes, except the verb ‘to look’, have a complex meaning structure.